Crime in the law enforcement agencies in 1948–1952 and its counteraction - V. A. Grechenko (Bulletin of Kharkiv National University of Internal Affairs)
The article reveals the state of crime in the police in 1948–1952, identifies its main manifestations and measures to counteract it. Crime in the police in the post-war years remained an acute and permanent problem. The late 1940s and early 1950s were no exception. This was influenced by the very nature of the totalitarian regime, which was based on violence and violation of the rule of law, the difficult socio-economic situation in the country, as the consequences of the post-war devastation were only beginning to be eliminated, and the low level of professional training and education of a certain number of police officers. For many of them, the perceptions of the state of legality were quite specific, formed mainly under the influence of the events of the war, combined with a tendency to be quick to punish those who were considered criminals and a relatively low level of awareness of the law. All of this has led to the existence of the problem of crime in the law enforcement agencies of the republic, and this problem is still relevant today, both from a theoretical and practical point of view. The most common violations in the police at that time were: alcoholism, abuse of office, connections with criminals, violations of the law during the detention of citizens and the conduct of investigations, failure to comply with orders, bribery, embezzlement, domestic and moral decay, desertion, disclosure of official secrets, unauthorised abandonment of duty, illegal use of weapons and, as a result, injury or killing of citizens, negligence in the performance of official duties, and loss of personal weapons. Most cases of lawbreaking were committed by police officers who were intoxicated. During this period, the Ministry of Internal Affairs of the Ukrainian SSR took a number of measures to improve the situation: offenders were dismissed from the police and brought to trial, and the leadership of those local police forces with the highest number of such violations was changed. This was done on the basis of an analysis of the flow of investigative cases, inspection of documentation and the state of work of local police bodies in the field of training their personnel.